Double Periodic Wave Solutions of the (2 + 1)-Dimensional Sawada-Kotera Equation - Zhonglong Zhao; Yufeng Zhang; Tiecheng Xia (Abstract and Applied Analysis)
Based on a general Riemann theta function and Hirota’s bilinear forms, we devise a straightforward way to explicitly construct double periodic wave solution of (2+1)-dimensional nonlinear partial differential equation. The resulting theory is applied to the (2+1)-dimensional Sawada-Kotera equation, thereby yielding its double periodic wave solutions. The relations between the periodic wave solutions and soliton solutions are rigorously established by a limiting procedure.